2016
DOI: 10.3889/oamjms.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Relation between microRNAs and Apoptosis in Hepatocellular Carcinoma

Abstract: AIM:To determine the relation between serum microRNAs and apoptotic markers as regards development of HCC to understand the underlying mechanism of HCV related hepatocarcinogenesis.PATIENTS AND METHODS:A total of 65 serum samples (25 samples from controls, 20 samples from hepatitis and 20 samples from HCC patients) were collected for miRNAs (mir 21, mir 199-a, and mir 155) detection. Human Programmed cell death protein-4 (PDCD-4) and Human Cytochrome-C (CYT-C) were determined.RESULTS:miRNAs 21 and 155 were ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…17,33 Different studies revealed the different roles of miRNAs in cancer growth through apoptosis. 25 Our study results confirm that miR-196a is mostly involved in the early stage of cell death in Huh 7.5 cells. Further research is suggested to better understand the effect of miR-196a on the pathway of cell death.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…17,33 Different studies revealed the different roles of miRNAs in cancer growth through apoptosis. 25 Our study results confirm that miR-196a is mostly involved in the early stage of cell death in Huh 7.5 cells. Further research is suggested to better understand the effect of miR-196a on the pathway of cell death.…”
Section: Discussionsupporting
confidence: 80%
“…The cells were inoculated with serum containing 10 5 HCV-RNA copies prepared from an HCVpositive blood. 25 The cells were plated in 10% DMEM and then passaged every 2-4 days. Using real-time PCR assay, the titer of progeny viruses was assessed.…”
Section: Hcv-rna Transfectionmentioning
confidence: 99%
“…miR-199a is significantly downregulated in the tissues and sera of patients with HCC. miR-199a may be used as a potential circulating biomarker for HCC (49,50). In the present study, downregulated miR-199a-5p elevated the expression of its targets CDK4 and IGF2.…”
Section: Discussionsupporting
confidence: 52%
“…Hsa-miR-21-5p is associated with tumors in several organs [ 25 ] and several liver diseases including nonalcoholic steatohepatitis [ 26 ], drug-induced liver injury [ 27 ], and hepatocellular carcinoma [ 28 , 29 ]. However, the relationship between hsa-miR-21-5p and autoimmune disease has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%